2021
DOI: 10.3390/microorganisms9102039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Live and Pasteurized Forms of Akkermansia from the Human Gut on Obesity and Metabolic Dysregulation

Abstract: Akkermansia muciniphila (A. muciniphila) is a promising probiotic candidate owing to its health-promoting properties. A previous study reported that the pasteurized form of A. muciniphila strains isolated from human stool samples had a beneficial impact on high-fat diet-induced obese mice. On the other hand, the differences in the probiotic effects between live and pasteurized A. muciniphila on the metabolism and immune system of the host are still inconclusive. This study examines the differences between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Interestingly, several studies have indicated that the outer membrane compounds of A. muciniphila , or pasteurized bacteria, have greater therapeutic potential for metabolic, inflammatory, and autoimmune diseases than live A. muciniphila ( 36 – 38 ). Notably, Kang et al.…”
Section: Role Of a Muciniphila In Protecting Again...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, several studies have indicated that the outer membrane compounds of A. muciniphila , or pasteurized bacteria, have greater therapeutic potential for metabolic, inflammatory, and autoimmune diseases than live A. muciniphila ( 36 – 38 ). Notably, Kang et al.…”
Section: Role Of a Muciniphila In Protecting Again...mentioning
confidence: 99%
“…In a murine model of obesity induced by HFD, it was demonstrated that treatment with A. muciniphila 10 8 –10 9 Colony-forming unit (CFU)/mL was able to reduce body weight gain, the accumulation of white adipose tissue (WAT), and energy efficiency and improve liver function impaired by HFD in mice ( Figure 1 ) ( 51 , 52 ). Furthermore, it was reported in the HFD-induced obesity model that the pasteurized form or AmOMV has been successful in reducing or preventing hepatic steatosis and adipogenesis/lipogenesis ( 38 , 53 ). In addition, the increase in Akkermansia ssp.…”
Section: Role Of a Muciniphila In Protecting Again...mentioning
confidence: 99%
See 1 more Smart Citation
“…A. muciniphila seems to be an irreplaceable member of healthy and balanced gut microbiota; furthermore, it alleviates mucosal inflammation either via microbe–host interactions associated with improved gut barrier function and reduction of inflammatory cytokines, or by improving the microbial community in UC. It is noteworthy that the beneficial effect of A. muciniphila was confirmed for both live and pasteurized forms used in different diseases, including liver injury [ 114 ], obesity, and diabetes 2 [ 115 , 116 , 117 ]. Ottman et al [ 118 ] identified a highly abundant outer membrane pili-like protein, Amuc-100, of A. muciniphila MucT, which through the activation of TLR-2 and TLR-4 induces the production of the regulatory cytokine IL-10 and could be directly responsible for the anti-inflammatory properties of the bacterium.…”
Section: Next Generation Probiotics and Ucmentioning
confidence: 99%
“…Most of these effects were linked to the high capacity of this strain to produce metabolites with anti-inflammatory effects. Clostridium butyricum is another potential non-traditional candidate probiotic that can produce metabolites with anti-inflammatory effects, such as butyrate ( 30 , 107 ).…”
Section: Precise Supplementary Strategiesmentioning
confidence: 99%